Temperature dependent local inhomogeneity and magnetic moments of (Li1−xFex)OHFeSe superconductors. Issue 9 (20th February 2023) - Tomassucci, G.; Tortora, L.; Pugliese, G. M.; Stramaglia, F.; Simonelli, L.; Marini, C.; Terashima, K.; Wakita, T.; Ayukawa, S.; Yokoya, T.; Kudo, K.; Nohara, M.; et al.
Abstract : Anomalous local structure and magnetic moment of an inhomogeneous FeSe based superconductor indicating importance of the structure and magnetic correlations in these materials. Abstract : We have combined the extended X-ray absorption fine structure (EXAFS) and X-ray emission spectroscopy (XES) to investigate the local structure and the local iron magnetic moments of (Li1− x Fe x )OHFeSe ( x ∼0.2) superconductors. The local structure, studied by Fe K-edge EXAFS measurements, is found to be inhomogeneous that is characterized by different Fe–Se bond lengths. The inhomogeneous phase exhibits a peculiar temperature dependence with lattice anomalies in the local structural parameters at the critical temperature T c (36 K) and at the spin density wave (SDW) transition temperature T N (130 K). Fe Kβ XES shows iron to be in a low spin state with the local Fe magnetic moment evolving anomalously as a function of temperature. Apart from a quantitative measurement of the local structure of (Li1− x Fe x )OHFeSe, providing direct evidence of nanoscale inhomogeneity, the results provide further evidence of the vital role that the coupled electronic, lattice and magnetic degrees of freedom play in the iron-based superconductors.